Buckling and wrinkling of thin membranes by using a numerical solver based on multivariate Taylor series. (November 2021) - Tian, H.; Potier-Ferry, M.; Abed-Meraim, F.
Highlights: A new numerical method combines Taylor series in space and in load parameter. It is applied to the Föppl-von Karman plate system. It permits to compute quasi perfect bifurcation problems. It permits to describe nearly flat states of a sheared membrane. Abstract: Buckling and wrinkling of thin structures often lead to very complex response curves that are hard to follow by standard path-following techniques, especially for very thin membranes in a slack or nearly slack state. Many recent papers mention numerical difficulties encountered in the treatment of wrinkling problems, especially with path-following procedures and often these authors switch to pseudo-dynamic algorithms. Moreover, the numerical modeling of many wrinkles leads to very large size problems. In this paper, a new numerical procedure based on a double Taylor series is presented, that combines path-following techniques and discretization by a Trefftz method: Taylor series with respect to a load parameter (Asymptotic Numerical Method) and with respect to space variables (Taylor Meshless Method). The procedure is assessed on buckling benchmarks and on the difficult problem of a sheared rectangular membrane.